Development of a mobile phone application - Chua, Jia Sheng (Nanyang Technological University, 2021)
In a fast-paced country like Singapore with city traffic, driving requires a lot of patience and being stuck in a jam so often means that you would have to cater more time for your journey. If you arrive at your destination but is unable to find a parking lot, drivers might have to source for other alternative carparks instead. This will be very daunting for drivers who have important appointments or if they have elderly or physically impaired passengers with them. With increasing petrol costs, time spent driving around looking for a carpark lot or idling while waiting for a parking lot to vacant might slowly add up to a significant amount in your monthly petrol costs.